Differential effects of once‐weekly glucagon‐like peptide‐1 receptor agonist dulaglutide and metformin on pancreatic β‐cell and insulin sensitivity during a standardized test meal in patients with type 2 diabetes. Issue 8 (16th May 2016) - Mari, A.; Del Prato, S.; Ludvik, B.; Milicevic, Z.; de la Peña, A.; Shurzinske, L.; Karanikas, C. A.; Pechtner, V.
Abstract : This substudy of the AWARD‐3 trial evaluated the effects of the once‐weekly glucagon‐like peptide‐1 receptor agonist, dulaglutide, versus metformin on glucose control, pancreatic function and insulin sensitivity, after standardized test meals in patients with type 2 diabetes. Meals were administered at baseline, 26 and 52 weeks to patients randomized to monotherapy with dulaglutide 1.5 mg/week (n = 133), dulaglutide 0.75 mg/week (n = 136), or metformin ≥1500 mg/day (n = 140). Fasting and postprandial serum glucose, insulin, C‐peptide and glucagon levels were measured up to 3 h post‐meal. β ‐cell function and insulin sensitivity were assessed using empirical variables and mathematical modelling. At 26 weeks, similar decreases in area under the curve for glucose [AUCglucose (0–3 h)] were observed among all groups. β ‐cell function [AUCinsulin /AUCglucose (0–3 h)] increased with dulaglutide and was unchanged with metformin (p ≤ 0.005, both doses). Dulaglutide improved insulin secretion rate at 9 mmol/l glucose (p ≤ 0.04, both doses) and β ‐cell glucose sensitivity (p = 0.004, dulaglutide 1.5 mg). Insulin sensitivity increased more with metformin versus dulaglutide. In conclusion, dulaglutide improves postprandial glycaemic control after a standardized test meal by enhancing β ‐cell function, while metformin exerts a greater effect on insulin sensitivity.